Home by morning - Warner, Kaki (Warner, Kaki. Heroes of Heartbreak Creek., 2015)
Consumed by her cause to help ex-slaves prepare for freedom, Prudence Lincoln must decide whether or not she is willing to give up everything for former Cheyenne warrior Thomas Redstone after he declares his love.